Identification, Silence, Separation, and Imagination: Children's Navigations of Christmas in a Religiously Diverse Norwegian Kindergarten - Ragnhild Laird Iversen (MDPI AG, 2023)
Christmas plays an important role in kindergartens in all the Nordic countries. While for many, Christmas is a time for belonging, for others it is a time for withdrawal or longing. This article applies ethnographic data to examine how staff and children manage Christmas in the context of a religiously diverse Norwegian kindergarten. Describing how Christmas dominates the kindergarten from late November and through December, I analyze how this affects children's practices, narratives, and opportunities to belong. Building on Yuval-Davies' concept of the politics of belonging, I develop a typology of four interrelated ways of navigation: identification, silence, separation, and imagination. This typology illuminates how children may be affected by the politics of belonging, but also how their agency and creativity lead to different ways of navigation, influencing processes of belonging. By providing a child-centered perspective on belonging, this article provides an empirically based contribution to discussions about inclusivity relating to religious and cultural diversity in ECEC.